Measurement of the human face using close-range digital photogrammetry technique - M. Ariff, M. Farid (2005)

(untitled)
In Malaysia, the data for craniofacial surgery is commonly obtained by using contact physical measurement of the facial features using calipers. This conventional contact method is not practical and time-consuming. Alternatively, a non-contact method such as close-range digital photogrammetry offers a new approach for such measurement. This research focuses on the measurement of the human face (soft tissue) using digital stereo-workstation known as Digital Video Plotter (DVP) to observe the stereo-images in 3D mode and acquire specific 3D spatial data of the face. To provide stereo-images of the face, the system configuration comprises of three pairs of digital cameras (Canon Ixus S500) and the object space control (control frame, camera platform and special chair). For analysis, the comparison is based on the measurement results (craniofacial landmark) between DVP and Calipers. The measurements using DVP are very stable and consistent as compared to the caliper. The 3D spatial data will then be used for further quantitative analysis for facial surgery and for the development of craniofacial database.